When can you expect contrast swing in a cricket game, and how to obtain it? - Tadrist, L.; Sampara, N.; Ashraf, I.; Andrianne, T. (Sports Engineering, 2020)
Curved trajectories are widely used in sports played with balls. Specifically, in cricket, balls are bowled with curved trajectories to surprise the batsman. Amongst the bowling techniques that provide curved trajectories, one of the most controversial is called contrast swing. This technique is specific to cricket and happens when the ball gets a nonuniform wear on each hemisphere after a few launches. The differential wear on the two sides of the cricket ball creates an aerodynamic side force. We quantify this force through wind tunnel experiments varying the roughness on one hemisphere of the ball. Trajectory modelling shows that this aerodynamic force is consistent with measurements on real throws. We also measure the side-to-side differential wear generated on a cricket ball as a function of the number of launches. Finally, we estimate the minimum velocity required to achieve contrast swing and the expected deviation as a function of launches number and game conditions.